Finding interval estimates involving nuisance parameters - Chiganova, Nadezhda (International Journal of Engineering and Technology, 2018)
The work establishes the assertions which, in a number of cases, allow to effectively determine the possibility of applying the method suggested in the work of L.N. Bolshev and E.A. Loginov â€œInterval estimates in the presence of interfering parameters. Probability theory and its applicationâ€ for constructing interval estimates of unknown parameters.Â Â